F194. Cerebellar contributions to somatosensory induced neuroplasticity. (May 2018) - Christova, Monica; Gallasch, Eugen; Pinter, Daniela
Abstract : Introduction: Monitoring, processing and integration of sensory inputs by the cerebellar circuitry is important for learning and adaptation in order to anticipate sensory events. The aim of this transcranial magnetic stimulation (TMS) study is to investigate the cerebellar involvement in the formation of cortical plasticity in response of vibrotactile hand stimulation. Such somatosensory-induced plasticity within the sensorimotor area was demonstrated in our previous studies. However, the afferent signals to the sensorimotor area are gated by extrinsic vertical pathways such as the cerebello-thalamo-cortical pathway, which raise the assumption of possible influence from subcortical relays along this neuronal route. Examining this hypothesis is of potential importance for patients with cerebellar lesions. Methods: The activation of the cerebello-thalamo-cortical networks in response to vibrotactile hand stimulation was assessed using TMS and twin coil for conditioning stimulation of the ipsilateral cerebellum and test stimulation of the contralateral motor cortex. Motor evoked potentials (MEP) were recorded from the right first dorsal interosseus muscle. The cerebellocortical inhibition (CBI) was tested before and after hand stimulation at 25 Hz for 20 min (HANDSTIM) versus SHAM in 14 healthy subjects in within subject design. Additionally vibration threshold (using a bone conduction probe of a clinical audiometer) and motor performance (Pegboard test) were evaluated. Results: Following HANDSTIM the normalized MEP amplitude was increased which shows reduced effect of CBI. The vibration threshold was decreased for 30 min while the Pegboard test motor performance remained unchanged. No effects were found in response to SHAM stimulation. Conclusion: The reduction of CBI in response to hand vibrotactile stimulation confirms the cerebellar involvement in mediating the sensory information to the cortex and will be compared in a follow-up study to patients with an infarct on the territory of the posterior inferior cerebellar artery. These patients often show sensorimotor/learning deficits, whereby the processes staying behind these effects are still not clarified.